Created in Japan : - Tatsuno, Sheridan M. (Harper & Row, 1960)
The Managerial Imperitive; The Sociocultural Challenges; The Creativity Paradox; The Technological Race; Conclusion. In this warning to U.S. business and policymakers, Tatsuno debunks the myth of the Japanese inability to innovate. Appendixes.